MODERN APPROACHES TO RECOGNITION AND MANAGEMENT OF MICROSCOPIC COLITIS - Kulchytska, O.M.; Kuzminova, N.V.; Lozynsky, S.E.; Knyazkova, I.I.; Poberezhets, O.L.; Nazarova, M.S.; Burdeina, L.V. (World of Medicine and Biology, 2024)
Microscopic colitis is an inflammatory bowel disease characterized by chronic diarrhea with specific microscopic changes in the absence of macroscopic (endoscopic) and radiological changes in the large intestine. Microscopic colitis is a fairly common disease, so physicians should be familiar with its clinical features and treatment strategies, as the disease deserves the same attention as classical inflammatory bowel disease. The article reviews the current understanding of microscopic colitis, the epidemiology of the disease, risk factors, clinical presentation, diagnostic criteria, and treatment strategies according to the European guidelines of the United European Gastroenterology Society and the European Microscopic Colitis Group 2021 with the overall goal of raising awareness and improving the rational treatment of microscopic colitis in clinical practice.